Hubungan Pola Makan dan Status Menstruasi terhadap Status Gizi pada Remaja di SMK Said Naum Jakarta Pusat Tahun 2023: The Relationship between Eating Patterns and Menstrual Status on the Nutritional Status of Adolescents at Said Naum Vocational School, Central Jakarta, 2023 - Fitria, Fitria Endah Purwani; Manurung, Chaterina; Fauziah, Shinta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
Menstrual disorders are one of the gynecological problems that require special attention because they often have an impact on the quality of life of adolescents or young adults and can be a serious indicator of the occurrence of a disease. According to data (Riskesdas, 2017) states that in Indonesia, women aged 10-59 years who experience regular menstruation are 68% and those who experience irregular menstrual problems within 1 year are 13.7%. Irregular menstrual problems at the age of 17-29 years and 30-34 years are quite a lot, namely 16.4%. Based on the results of a preliminary study at a high school in Jakarta, 42% of female students experienced an abnormal menstrual cycle. Based on the exposure, it is necessary to carry out an analysis related to the relationship between nutritional status and the menstrual cycle in female students at SMK Said Naum, Central Jakarta. This research is a quantitative analytic research with cross-sectional method. A sample of 42 young women with total sampling technique. Data was taken by using primary data via a google form questionnaire. The results of the study showed that the majority of respondents were 16 years old, as many as 36 people (55.7%), and young women with unhealthy eating patterns, as many as 27 people (64.3%). the most nutritional status of young women in the thin category, namely 21 people (9.5%). Based on statistical tests, it can be found that there is no relationship between menstrual status and nutritional status in adolescents at Said Naum Vocational School, Central Jakarta in 2023. ABSTRAK Gangguan menstruasi merupakan salah satu masalah ginekologik yang memerlukan perhatian khusus karena sering kali berdampak terhadap kualitas hidup remaja atau dewasa muda dan dapat menjadi indikator serius terjadinya suatu penyakit. Menurut data (Riskesdas, 2017) menyebutkan bahwa di Indonesia, wanita usia 10-59 tahun yang mengalami menstruasi teratur sebanyak 68% dan yang mengalami masalah menstruasi tidak teratur dalam 1 tahun adalah 13,7%. Masalah haid tidak teratur pada usia 17-29 tahun dan usia 30-34 tahun cukup banyak yaitu sebesar 16,4%. Berdasarkan hasil studi pendahuluan di SMU diJakarta di dapatkan 42% siswi mengalami siklus menstruasi yang tidak normal. Berdasarkan paparan perlu dilakukan analisis terkait hubungan antara status gizi dengan siklus menstruasi pada siswi SMK Said Naum Jakarta Pusat. Penelitian ini merupakan penelitian analitik kuantitatif dengan metode cross-sectional. Sampel sebanyak 42 remaja putri dengan teknik total sampling. Data diambil dengan menggunakan data primer melalui kuesioner google form. menunjukkan umur responden mayoritas berumur 16 tahun sebanyak 36 orang (55,7%), Remaja putri dengan pola makan yang tidak baik sebanyak 27 orang (64,3%). status gizi pada remaja putri terbanyak dalam kategori kurus yaitu 21 orang (9,5%). Berdasarkan uji statistik dapat ditemukan bahwa tidak terdapat hubungan antara status menstruasi dengan Status Gizi Pada Remaja di SMK Said Naum Jakarta Pusat Tahun 2023.